Added Value Analysis and Affecting Factors in Coconut Sugar Processing - Shofia Nur Awami; Amila Layaliya Faza (Institut Pertanian Bogor, 2025)
The general goal of processing coconut sugar obtained from coconut sap is to maximize its added value. Purbalingga Regency is a major producer of coconut sugar in Central Java. Molded coconut sugar is the most commonly produced variety of coconut sugar. The purpose of this study is to determine the added value of the coconut brown sugar processing industry, as well as the elements that influence it. The Hayami method of added value analysis was applied, as well as multiple linear regression analysis. The research employed up to 36 coconut brown sugar craftspeople and took place between February and March 2021. The results showed that processing coconut sap adds Rp. 689.81 per kilogram, with an added value ratio of 34.86 percent. The value added category falls into the medium group. Production capacity, raw materials, output price, raw material costs, and other input prices all have a substantial impact on the added value of converting coconut sap to sugar. Keywords: coconut sap, added value, coconut sugar, Hayami